Nuclear quantum effects on the structure and the dynamics of [H2O]8 at low temperatures - Videla, Pablo Ernesto (2013)
We use ring-polymer-molecular-dynamics (RPMD) techniques and the semi-empirical q-TIP4P/F water model to investigate the relationship between hydrogen bond connectivity and the charac- teristics of nuclear position fluctuations, including explicit incorporation of quantum effects, for the energetically low lying isomers of the prototype cluster [H2O]8 at T = 50 K and at 150 K. Our results reveal that tunneling and zero-point energy effects lead to sensible increments in the magnitudes of the fluctuations of intra and intermolecular distances. The degree of proton spatial delocalization is found to map logically with the hydrogen-bond connectivity pattern of the cluster. Dangling hydro- gen bonds exhibit the largest extent of spatial delocalization and participate in shorter intramolecular O-H bonds. Combined effects from quantum and polarization fluctuations on the resulting individ- ual dipole moments are also examined. From the dynamical side, we analyze the characteristics of the infrared absorption spectrum. The incorporation of nuclear quantum fluctuations promotes red shifts and sensible broadening relative to the classical profile, bringing the simulation results in much more satisfactory agreement with direct experimental information in the mid and high fre- quency range of the stretching band. While RPMD predictions overestimate the peak position of the low frequency shoulder, the overall agreement with that reported using an accurate, parame- terized, many-body potential is reasonable, and far superior to that one obtains by implementing a partially adiabatic centroid molecular dynamics approach. Quantum effects on the collective dynam- ics, as reported by instantaneous normal modes, are also discussed